Command CV:A Legend by Default. - Whitlaw, Robyn; Mandiberg, Michael (Afterimage, 2002)
Discusses the conflicts on the representation and ownership of three copies of a photograph named differently by photographers Walker Evans, Sherrie Levine and Michael Mandiberg. Origin of each copy; Discussion on the ownership violations made by Levine and Mandiberg; View on the conflict.